Registration of 'Northern' Hard Red Winter Wheat. Issue 2 (11th March 2016) - Berg, J. E.; Lamb, P. F.; Miller, J. H.; Wichman, D. M.; Kephart, K. D.; Stougaard, R. N.; Pradhan, G. P.; Nash, D. L.; Grey, W. E.; Gettel, D.; Gale, S.; Jin, Y.; et al.
Abstract : 'Northern' (Reg. No. CV‐1114, PI 676026) hard red winter wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Station in 2015. Northern was derived from a composite of two crosses, MT9982//MTW0072/NW97151 and MTW0047//MTW0072/NW97151. Northern was developed using a modified bulk breeding method and selected as an F5:7 headrow. Northern was tested under the experimental number MT0978 in Montana yield trials from 2009 to 2015. Like predominant cultivar Yellowstone, Northern is a high‐yielding, winter‐hardy hard red winter wheat cultivar with medium to late maturity, medium to high grain protein, and acceptable milling and baking quality. Northern was released for its excellent performance in winter wheat production environments of north‐central Montana, reduced plant height, and improved grain volume weight and resistance to stem rust (caused by Puccinia graminis Pers.:Pers. f. sp. tritici Eriks. & E. Henn.) relative to Yellowstone.